Integrating the Theory of Planned Behavior to Understand Muslim Tourist Behavior in Halal Tourism Destinations - Suro, Lulu Ilmang; Armiani, Armiani (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to systematically review the literature published in the last 10 years on the Theory of Planned Behavior integration to understand Muslim travelers’ behavior in halal tourism. The design of this study uses a systematic literature review method. The excellence of the study was assessed by studying the year of publication, journal of publication, country of study, type of statistical method, data collection technique, and content analysis in the literature on Muslim travelers’ behavior in halal tourism. This study is based on 25 selected articles published in peer-reviewed journals between 2015 and 2024. The results show that Muslim travelers’ decisions in choosing halal tourism destinations are greatly influenced by the interaction between their attitudes towards halal facilities, social norms in the community, and the obstacles they feel in accessing the destination. Thus, halal tourism destination managers need to pay attention to these three factors simultaneously to increase the attractiveness of the destination for Muslim tourists.